A Meta‐Analysis to Estimate the Placebo Effect in Randomized Controlled Trials in Juvenile Idiopathic Arthritis. Issue 6 (26th May 2016) - Demirkaya, Erkan; Lanni, Stefano; Bovis, Francesca; Galasso, Roberta; Ravelli, Angelo; Palmisani, Elena; Consolaro, Alessandro; Pederzoli, Silvia; Marafon, Denise; Simianer, Stefan; Martini, Alberto; Ruperto, Nicolino; et al.
Abstract : Objective: To estimate the placebo effect in juvenile idiopathic arthritis (JIA) through a meta‐analysis of phase III clinical trials with placebo comparator. Methods: A systematic literature search was carried out up to December 2014. For parallel design studies the outcome was evaluated as a single 1‐dimensional (1‐D) variable or as a composite score; outcomes of withdrawal studies were evaluated only as composite scores. Results: We included 26 of 224 trials (12%). In trials with parallel study design and a 1‐D outcome, the placebo effect was 0.35 (95% confidence interval [95% CI] 0.27–0.43). Among trials with parallel study design and a composite score outcome, the placebo rate response was higher in trials that included patients with nonsystemic JIA (0.35 [95% CI 0.29–0.42]) than in trials that included only patients with systemic JIA (0.17 [ 95% CI 0.10–0.30]). In the withdrawal design trials, the percentages of patients receiving placebo who had disease flares during the double‐blind phase were lower in trials that included patients with nonsystemic JIA (0.55 [ 95% CI 0.47–0.64]) than in trials that included only patients with systemic JIA (0.68 [95% CI 0.33–0.90]). Conclusion: In trials with a parallel study design a sizable number of patients seem to benefit from a placebo effect, although this effect is smaller in patients with systemic JIA. In trials with a withdrawal design the inverse placebo effect is similar among the different JIA categories. This placebo effect should be considered when evaluating the effectiveness of proposed interventions and for future calculations of sample size.